The value of voluntary vs. mandatory responsible gambling limit-setting systems: A review of the evidence. Issue 2 (4th May 2021) - Delfabbro, Paul H.; King, Daniel L
ABSTRACT: Pre-commitment and limit-setting schemes have been widely discussed as potentially useful responsible gambling tools to minimize the financial harm associated with excessive gambling. Such systems allow gamblers to set time or monetary limits and can be implemented in a voluntary or mandatory form. Previous reviews have suggested that these technologies, particularly when applied as voluntary systems, appear to have little empirical support because of low uptake rates and limitations in research studies. Using evidence drawn from peer-reviewed and online literature, we examine developments over the last decade. We provide an updated appraisal of pre-commitment technology that encompasses more recent trials. We also include studies of online limit setting and the studies of mandatory limits in Norway. The present analysis finds general support for the conclusions of previous reviews and confirms the potential benefits of mandatory systems. It also highlights some potential selective uses for voluntary systems while also noting potential risks associated with implementing mandatory global limits.